Penerapan Higiene Sanitasi Makanan pada Rumah Makan di Tempat Wisata - Rahmawati, Kurnia; Siwiendrayanti, Arum (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: According to Kendal Regency health profile data in 2018, the number of Food Processing Places (TPM) examined as many as 2,538 places, and 63.40% who have met the health requirements. The purpose of this study was to determine the factors associated with the application of food sanitation hygiene in restaurants in Ngebum Beach, Kaliwungu District, Kendal Regency. Methods: This research is an observational study with a cross-sectional approach. The data collection technique was carried out by observing and interviewing 30 samples of food handlers at Ngebum Beach. Sampling was done by total sampling technique, then the data were analyzed by univariate and bivariate. Furthermore, the data is presented in tabular form and concluded. Results: There is a relationship between the attitudes of food handlers (p-value = 0.003), and participation in training (p-value = 0.033) with the application of food sanitation hygiene. And there is no relationship between the level of knowledge ( p value = 0,04), number of visitors (p-value = 0.328) and years of service (p-value = 1,000) with the application of food sanitation hygiene. Conclusion: To increase supervision and guidance both by restaurant owners, health centers, and local related agencies.